Telecollaboration: Creating International Bridges in Socially Distanced Times - Úna Rose Carthy (The Irish Association for Applied Linguistics, 2021)
Since it emerged in the 1990s, telecollaboration has evolved from being the reserve of linguists and language educators to a more broadly applicable approach that can be used in diverse academic contexts. Web 2 technologies have been used to transform learning spaces, by creating dynamic communication channels and authentic interaction. This project report describes a recent transnational exchange project (TEP). The TEP created a much-needed alternative to Erasmus mobility for students whose year abroad was abruptly aborted in March 2020, effectively harnessing Web 2 technologies to create social presence in socially distanced times.